Recent advance in the field of pathogenesis of diarrhoea caused by Escherichia coli - Halil Ozerol, I.; Ozbilge, Hatice (Annals of Medical Research, 2021)
None
Keywords: s : Enterotoxigenic E.coli (ETEC), enteropathogenic E.coli (EPEC), enteroinvasive E.colı (EIEC). enterohaemorrhagic E.coli (EHEC), enteroaggregative E.coli (EAggEC)